TINJAUAN HUKUM ISLAM TERHADAP PENUKARAN POINT DENGAN UANG PADA APLIKASI TIK-TOK PERSPEKTIF AKAD MUAMALAH - Muhammad Shobirin; Abdul Hafiz (Universitas Islam Negeri Mataram, 2024)
This study discusses an overview of Islamic law on exchanging points for money in the Tik-Tok application from the perspective of a muamalah contract. This research method is a type of case study which is included in qualitative research. The author in this study is descriptive where most of the data used comes from interviews, observations in the form of sentences or narratives. From the results of this study, it says that exchanging points for money on the Tik-Tok application is a job/mission where users must complete the work to get rewards from tiktok such as: inviting new users, watching videos, uploading videos, live streaming and tiktok affiliates. Gifts or wages are permitted in Islam if there is no other purpose or purpose except for good intentions.